Pengaruh Electronic Word of Mouth (E WOM), Customer Rating, dan Discount terhadap Keputusan Pembelian Konsumen pada Platform E Commerce (Studi pada Masyarakat Nagari Batuhampar Kecamatan Akabiliru) - Teguh Tri Rizki; Cahya Agung Mulyana (ARZUSIN, 2026)
Consumer purchasing decisions on e-commerce platforms have received attention in various previous studies. However, studies that specifically analyze the effect of Electronic Word of Mouth (E-WOM), customer rating, and discounts on the purchasing decisions of communities in rural areas, particularly Nagari Batuhampar, remain limited. This study aims to analyze the effect of E-WOM, customer rating, and discounts on consumer purchasing decisions on e-commerce platforms, both partially and simultaneously. This study used a quantitative approach with a cross-sectional survey design. The sample consisted of 97 respondents selected using purposive sampling. Data were collected using a Likert-scale questionnaire that had met the validity and reliability tests, and were then analyzed using multiple linear regression with the assistance of IBM SPSS. The results show that E-WOM (β = 0.403; p = 0.013) and discounts (β = 0.485; p < 0.001) have a positive and significant effect on purchasing decisions, whereas customer rating (β = 0.189; p = 0.188) has no significant effect. Simultaneously, E-WOM, customer rating, and discounts have a significant effect on purchasing decisions. These findings strengthen consumer behavior theory by showing that digital information and promotional strategies are important determinants in shaping purchasing decisions on e-commerce platforms. The conclusion of this study emphasizes the importance of optimizing E-WOM and discount strategies in improving consumer purchasing decisions. The implications of this study include theoretical contributions to the development of digital marketing literature as well as practical implications for business actors and e-commerce platform managers in optimizing customer reviews and discount-based promotional strategies. Future research is recommended to expand the research area, increase the number of respondents, and include other variables that may potentially influence purchasing decisions.